2010
DOI: 10.1007/s12032-010-9707-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of p39 is associated with a poor prognosis in human hepatocellular carcinoma

Abstract: The aims of this study are to investigate the relationship between p39 expression and clinicopathological parameters of hepatocellular carcinoma (HCC) and to evaluate the prognostic value of p39 for HCC patients. Real-time quantitative PCR and immunohistochemistry was used to measure p39 expression in tumor and adjacent nontumor samples. Relationships of p39 expression with clinical parameters and patient survival were analyzed. Real-time quantitative RT-PCR showed that the quantity of p39 mRNA in cancerous ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
(71 reference statements)
0
13
0
Order By: Relevance
“…CDK5 and p35 were recently identified as a potent tumor suppressor in HCC. The decreased expression of p39 correlated with a poor overall survival rate [ 31 ]. Regulation of CDK5 activity promoted the proliferation of medullary thyroid carcinoma (MTC) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDK5 and p35 were recently identified as a potent tumor suppressor in HCC. The decreased expression of p39 correlated with a poor overall survival rate [ 31 ]. Regulation of CDK5 activity promoted the proliferation of medullary thyroid carcinoma (MTC) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In tissues from non-small cell lung cancer (NSCLC), breast, brain and nasopharyngeal cancer patients, increased Cdk5 and/or activator expression parallels advanced cancer stages, occurrence of lymph node metastasis, and overall poor 5-year survival, while low Cdk5 levels correlates with metastatic-free disease [14–19]. Somewhat remarkably abnormal low Cdk5 or activator tumor levels are also indicative of poor prognosis as in advanced gastric cancer [20] or hepatocellular carcinoma (HCC) [21]. More studies are needed to understand the molecular mechanisms by which Cdk5 and activators contribute to these cancers.…”
Section: Human Cancers Express Cdk5mentioning
confidence: 99%
“…Changes in the phosphorylation status are often accompanied with transcription factor regulation. Indeed, it has been shown that USF2 is a phosphoprotein [28,29] and that a number of tumor entities such as prostate cancer [30,31,32,33], hepatocellular carcinoma [34,35,36,37] and breast cancer [38,39,40] are associated with an aberrant USF2 function (for review see [13]). In addition, these cancers are also associated with high expression and activity levels of cyclin-dependent kinase-5 (CDK5) (for review see [41])).…”
Section: Introductionmentioning
confidence: 99%